Loss of Temperature Compensation of Circadian Period Length in the frq-9 Mutant of Neurospora crassa - Jennifer Loros; Jerry F. Feldman (1986)
A new circadian clock mutant of Neurospora crassa has been isolated, whose most distinctive characteristic is the complete loss of temperature compensation of its period length. The Q10 of the period length was found to be equal to about 2 in the temperature range from 18 degrees to 30 degrees C. The period length was also found to be dependent on the composition of the medium, including the nature and concentration of both the carbon source and the nitrogen source. Although the rate of the clock and the growth rate were directly related when affected by varying the temperature, they were inversely related when altered by changing the composition of the medium. Therefore, the mutation has not simply coupled clock rate to growth rate in this strain. The mutation maps to the frq locus, where seven other clock mutations previously studied also map. Therefore, this mutant has been called frq-9. Since several of the other frq mutants show partial loss in temperature compensation, it is suggested that the frq gene or its product is closely related to the temperature compensation mechanism of the circadian clock of Neurospora.